How Firm Size Moderates Low-Cost Growth and Non-Performing Loans in Determining Bank Profitability - Fitriana, Ade; Nugroho, Lucky (Social and Economic Bulletin, 2025)
This study aims to analyze the effect of low-cost funds, credit distribution growth, and non-performing loans on bank profitability as measured by Return on Assets (ROA), and to examine the role of firm size as a moderating variable. The research was conducted on 18 banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study employed a quantitative approach using multiple linear regression and Moderated Regression Analysis (MRA). The results show that low-cost funds and credit growth have a significant positive effect on profitability (ROA), while non-performing loans have a significant negative effect. Furthermore, firm size moderates the relationship between the independent variables and profitability, indicating that larger banks are more capable of optimizing low-cost funding and credit expansion while mitigating the negative impact of non-performing loans. These findings provide managerial implications for banking institutions to enhance profitability through efficient fund management, prudent lending, and effective risk control. For regulators, the results offer insights into developing supervision policies that consider firm size as a determinant of financial performance and stability.